The First Female Academics in Programs of Educational Administration in Canada: Riding waves of opportunity - Wallace, Janice; Wallin, Dawn; Viczko, Melody; Anderson, Heather (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
Our research situates, contextualizes, and analyzes the lived experiences of ten female academics who were among the first women in the academic discipline of educational administration in seven of the ten provinces in Canada. Using institutional ethnography and life history to inform our analysis, this article explores three of the themes that emerged from participant interviews in the first stage of a multi-stage research process: mapping careers, transforming knowledge, and negotiating institutional tensions between the personal and professional aspects of their work.